2012
DOI: 10.1007/s11307-012-0572-0
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Radiologic Interventions and 18F-DOPA PET in Diagnosing and Localizing Focal Congenital Hyperinsulinism: Systematic Review and Meta-Analysis

Abstract: PurposeThis systematic review and meta-analysis aimed to quantify the diagnostic performance of pancreatic venous sampling (PVS), selective pancreatic arterial calcium stimulation with hepatic venous sampling (ASVS), and 18F-DOPA positron emission tomography (PET) in diagnosing and localizing focal congenital hyperinsulinism (CHI).ProceduresThis systematic review and meta-analysis was conducted according to the PRISMA statement. PubMed, EMBASE, SCOPUS and Web of Science electronic databases were systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 46 publications
3
36
0
15
Order By: Relevance
“…Fernandez-Marmiesse et al (10) reported five patients with paternally inherited K ATP mutations and whose post pancreatectomy pathology result was not consistent with that of focal lesion. Similar findings have been reported by other studies (1,21,27,30). There are a number of possible mechanisms as to how a heterozygous ABCC8/KCNJ11 mutation can lead to diffuse disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Fernandez-Marmiesse et al (10) reported five patients with paternally inherited K ATP mutations and whose post pancreatectomy pathology result was not consistent with that of focal lesion. Similar findings have been reported by other studies (1,21,27,30). There are a number of possible mechanisms as to how a heterozygous ABCC8/KCNJ11 mutation can lead to diffuse disease.…”
Section: Discussionsupporting
confidence: 90%
“…Before the advent of 18 F DOPA-PET CT, pancreatic venous sampling (PVS) and selective pancreatic arterial calcium stimulation with hepatic venous sampling (ASVS) were used to differentiate between the two subtypes (25,26). A recent systematic review and meta-analysis has found 18 F DOPA-PET CT to be far superior to PVS and ASVS in diagnosing and localising focal CHI (27).…”
Section: Introductionmentioning
confidence: 99%
“…До недавнего времени в клинической практике для дифференциальной диагностики диффузной и фокальной форм ВГИ использова-лись методики, основанные на определении уровня инсулина в пробах крови, оттекающей от поджелудочной железы: чрескожно-чреспеченочный забор крови из ветвей ворот-ной вены (ЧЧЗКВ) и забор крови из правой пе-ченочной вены после внутриартериальной сти-муляции (АСЗК) кальцием различных отделов поджелудочной железы [16,17,18]. Чувстви-тельность ЧЧЗКВ и АСЗК составляет 87 и 71%, соответственно [16].…”
unclassified
“…Чувстви-тельность ЧЧЗКВ и АСЗК составляет 87 и 71%, соответственно [16]. Специфичность данных методов варьирует в различных литературных источниках.…”
unclassified
See 1 more Smart Citation